MODEL-MODEL PENILAIAN SENGKETA TINDAKAN FAKTUAL OLEH HAKIM PENGADILAN TATA USAHA NEGARA - Tahir, Erdin; Fathammubina, Rohendra; Arifin, Jajang (Yustitia, 2024)
The presence of Law No. 30 of 2014 on Government Administration that expands the meaning of state administrative decisions is not only interpreted as decisions in written form but includes factual actions. This of course also expands the authority of the State Administrative Court (PTUN). However, factual actions are not expressly mentioned in the Law. Therefore, what is interesting in this article is to clarify what factual action means. Then analyze the judge's style in deciding the object of the factual action dispute. The results of this study resulted in two conclusions, first, there are six characteristics of factual actions, namely actions or actions in public jurisdiction, actions or actions that are concrete/real, carried out by government officials/bodies, do not have legal effects, and cause factual effects. Second, there are five models of assessment of factual actions by judges at the PTUN. These five models of assessment are carried out on the same object of dispute, but PTUN judges have different grounds for consideration in deciding cases of factual action disputes. This assessment model is carried out on six PTUN decisions as material for study in this article. So that knowing the judge's assessment models, strengthens our understanding of the resolution of factual action disputes both in terms of concepts and practices at the PTUN